Measles immunity gaps and the progress towards elimination: a multi-country modelling analysis. Issue 10 (October 2017) - Trentini, Filippo; Poletti, Piero; Merler, Stefano; Melegaro, Alessia
Summary: Background: The persistent circulation of measles in both low-income and high-income countries requires a better characterisation of present epidemiological trends and existing immunity gaps across different sociodemographic settings. Serological surveys, which provide direct measures of population protection against the infection, are underexploited and often supply fragmentary estimates of population immunity. This study aims to investigate how measles immunity has changed over time across different socioeconomic settings, as a result of demographic changes and past immunisation policies. Methods: For this multi-country modelling analysis, we developed a transmission model to simulate measles circulation during the past 65 years in nine countries with distinct demographic and vaccination histories. The model was calibrated on historical serological data and used to estimate the reduction of disease burden as a result of vaccination and present age-specific residual susceptibility. Findings: Our model shows that estimated residual susceptibility to measles ranges from 3% in the UK to more than 10% in Kenya and Ethiopia. In high-income countries, such as Italy, Singapore, and South Korea, where routine first-dose administration produced more than 90% of immunised individuals, only about 20% of susceptible individuals are younger than 5 years. We also observed that the reduction in fertility that has occurred during the past decades in high-income countries has contributed to almost half of the reduction in measles incidence. In low-income countries, where fertility is high, the population is younger and routine vaccination has been suboptimum. Susceptible individuals are concentrated in early childhood, with about 60% of susceptible individuals in Ethiopia younger than 10 years. In these countries, Supplementary Immunization Activities (SIAs) were responsible for more than 25% of immunised individuals (up to 45% in Ethiopia), mitigating the consequences of suboptimum routine vaccination coverage. Interpretation: Future vaccination strategies in high-fertility countries should focus on increasing childhood immunisation rates, either by raising first-dose coverage or by making erratic SIAs more frequent and regular. Immunisation campaigns targeting adolescents and adults are required in low-fertility countries, where the susceptibility in these age groups will otherwise sustain measles circulation. Funding: European Research Council.